Physical, chemical and biological quality of a litholic neosol under integrated crop-livestock in the Pampa Biome (Research, Society and Development, 2020)
This study aimed to evaluate the physical, chemical and biological quality on a Litholic Neosol in family farmers under integrated crop-livestock systems located in Pampa Biome, defining which of these indicators are able to detect the effect of the different management practices adopted in different use systems: native grazed field, ryegrass pasture and corn. Soil samples were collected in the layers from 0.00-0.05 m, 0.05-0.10 m and 0.10-0.20 m to quantify the bulk density, total porosity, diameter weighted average, total organic carbon, total nitrogen, carbon of the coarse fraction, carbon associated with minerals, carbon of the free light fraction, carbon of the free occlude fraction, carbon of the heavy fraction, microbial biomass carbon and basal soil respiration. The factorial analysis showed that the “Organic Matter Factor”, “Light Organic Matter” and “Humified Carbon” being the most sensitive to detect the effects of the different management practices used. The indicators that compose the “Organic Matter Factor” are more associated to the native grazed field system and those that compose the “Aggregation Factor”, “Granulometric Fractions Factor” and “Total Porosity Factor” are more associated to the ryegrass pasture system and corn system. The bulk density, the heavy fraction of organic matter and the microbial carbon are related to the three use soil use systems.